Healthy Air for Children: Strategies for Ventilation and Air Cleaning to Control Infectious Respiratory Particles in School Classrooms - Ding, Er (A+BE | Architecture and the Built Environment, 2025)
In response to the WHO and UN’s call to ensure children’s right to breathe “clean” air and the challenges posed by the COVID-19 pandemic on maintaining healthy indoor air quality (IAQ), this PhD research explores ventilation and air cleaning strategies to control the spread of infectious respiratory particles (IRPs) in school classrooms. The study follows four key steps: (1) a literature review bridging school ventilation regimes, IRP transmission, and advanced ventilation systems; (2) a field study to evaluate real-world ventilation and thermal conditions during the pandemic; (3) an experimental investigation of performance of mobile air cleaners (MACs) followed by an in-situ validation; and (4) a combined experimental and computational study to assess personalized air cleaners (PACs) as localized exhaust for IRP removal. Findings reveal that most classrooms rely on natural ventilation, often failing to meet IAQ standards, especially when fully occupied. With windows and doors open, ventilation rates remained inconsistent, and thermal conditions were unsatisfactory. Hence, more controllable ventilation and air cleaning approaches are needed. MACs, when appropriately selected and positioned, offer effective protection against long-range IRP transmission at room scale, while PACs are effective at mitigating localized, short-range IRP exposure, improving IAQ at an individual level. This research offers a comprehensive set of solutions for IRP control in classrooms, with actionable insights for a variety of stakeholders. It advocates for a shift from comfort-based to health-centered paradigms. Future research should explore hybrid systems, optimize designs, and validate interventions through real-world infection risk assessments to create healthier, more resilient classrooms.